Cardiac and intestinal tissue conduct developmental and reparative processes in response to lymphangiocrine signaling - Kurup, Shreya; Tan, Can; Kume, Tsutomu (Frontiers in Cell and Developmental Biology, 2023)
Lymphatic vessels conduct a diverse range of activities to sustain the integrity of surrounding tissue. Besides facilitating the movement of lymph and its associated factors, lymphatic vessels are capable of producing tissue-specific responses to changes within their microenvironment.Lymphatic endothelial cells (LECs) secrete paracrine signals that bind to neighboring cellreceptors, commencing an intracellular signaling cascade that preludes modifications to the organ tissue's structure and function. While the lymphangiocrine factors and the molecular and cellular mechanisms themselves are specific to the organ tissue, the crosstalk action between LECs and adjacent cells has been highlighted as a commonality in augmenting tissue regeneration within animal models of cardiac and intestinal disease. Lymphangiocrine secretions have been owed for subsequent improvements in organ function by optimizing the clearance of excess tissue fluid and immune cells and stimulating favorable tissue growth, whereas perturbations in lymphatic performance bring about the opposite. Newly published landmark studies have filled gaps in our understanding of cardiac and intestinal maintenance by revealing key players for lymphangiocrine processes. Here, we will expand upon those findings and review the nature of lymphangiocrine factors in the heart and intestine, emphasizing its involvement within an interconnected network that supports daily homeostasis and self-renewal following injury.